Retailing in the 21st century - Thomas, Chris (Wiley, 2006)
This book will help students understand how to start a retail business from the ground up. The authors' focus throughout the book is on being organized and purposeful and knowing every step of the way where the business is going and why. The major goals include learning to strategize, expect the best but prepare for the worst, create a positive work environment, and keep yourself and your staff motivated to find the best merchandise and offer it enthusiastically to your customers at a fair price. After reading this book, students will be prepared to be a successful retailer in the 21st century.